2017
DOI: 10.1177/014556131709600105
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Fungal Laryngopharyngitis Resulting in Laryngeal Destruction with Complete Laryngotracheal Separation: Report of a Case

Abstract: As the treatment of hematopoietic cancers evolves, otolaryngologists will see a higher incidence of opportunistic infections. We discuss a case of invasive fungal disease that invaded the larynx, pharynx, trachea, and pulmonary parenchyma after chemotherapy. The patient, a 46-year-old woman, presented 1 week after undergoing induction chemotherapy. Her initial symptoms were odynophagia and dysphagia. Despite encouraging findings on physical examination, her health rapidly declined and she required an urgent tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The most studied site of invasive fungal infection remains sinonasal, but other sites have also been described, including the larynx, tracheobronchial tree, 2,3 thyroid, periorbital region, and adenoids 4,5 . To our knowledge, this is the first description of invasive fungal pharyngitis in a pediatric patient, and the second report of a patient with invasive fungal pharyngitis 6 …”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The most studied site of invasive fungal infection remains sinonasal, but other sites have also been described, including the larynx, tracheobronchial tree, 2,3 thyroid, periorbital region, and adenoids 4,5 . To our knowledge, this is the first description of invasive fungal pharyngitis in a pediatric patient, and the second report of a patient with invasive fungal pharyngitis 6 …”
Section: Discussionmentioning
confidence: 80%
“…4,5 To our knowledge, this is the first description of invasive fungal pharyngitis in a pediatric patient, and the second report of a patient with invasive fungal pharyngitis. 6 The treatment strategy for invasive fungal disease is immediate aggressive surgical debridement and broad antifungal therapy. Patients who have diabetes undergo surgical resection, younger age, and have an ANC > 500/mcL have an improved prognosis compared to those unable to undergo surgery in invasive fungal sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…Revising the literature, ulcerative disruption of respiratory tract, descending from invasive Aspergillus laryngotracheal infection, are reported in adults [e.g., (9,10,14,20,25,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)] and in adolescents (15 and 17 years old) (47,48) but not in pediatric patients. According to our knowledge, only Barnes et al (49) and Athanassiadou et al (50) described Aspergillus laryngotracheobronchitis in children (6 and 2 years old) affected by acute lymphocytic leukemia; however, in these cases, the characterizing elements included plaques and necrotic cells, whereas ulcerative lesions were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…In that case, the perforation was successfully repaired and resolved using a pedicle muscular flap ( latissimus dorsi ) and temporary airway stenting. Additionally, Swiss et al ( 44 ) reported about an invasive Aspergillus laryngopharyngitis affecting an immunocompromised woman (history of myelodysplastic syndrome and acute myelogenous leukemia) and leading to autolaryngectomy: laryngeal destruction up to complete laryngotracheal separation were observed. The patient survived by aggressive antifungal therapy and surgical debridement.…”
Section: Discussionmentioning
confidence: 99%